3D‐printed individual labware in biosciences by rapid prototyping: A proof of principle. Issue 1 (22nd August 2014) - Lücking, Tim H.; Sambale, Franziska; Beutel, Sascha; Scheper, Thomas
<x xml:space="preserve">Abstract</x> The fabrication of individual labware is a sophisticated task that requires dedicated machines and skills. Three‐dimensional (3D) printing has the great potential to simplify this procedure drastically. In the near future, scientists will design labware digitally and then print them three dimensionally directly in the laboratory. With the available rapid prototyping printer systems, it is possible to achieve this. The materials accessible meet the needs of biotechnological laboratories that include biocompatibility and withstanding sterilization conditions. This will lead to a completely new approach of adapting the labware to the experiment or even tailor‐made it to the organism it is being used for, not adapting the experiment to a certain standard labware. Thus, it will encourage the creativity of scientists and enrich the future laboratory work. We present different examples illustrating the potential and possibilities of using 3D printing for individualizing labware. This includes a well plate with different baffle geometries, shake flask cap with built‐in luer connections, and filter holder for an in‐house developed membrane reactor system.